RBM20 phosphorylation and its role in nucleocytoplasmic transport and cardiac pathogenesis. Issue 5 (8th April 2022) - Zhang, Yanghai; Wang, Chunyan; Sun, Mingming; Jin, Yutong; Braz, Camila Urbano; Khatib, Hasan; Hacker, Timothy A.; Liss, Martin; Gotthardt, Michael; Granzier, Henk; Ge, Ying; Guo, Wei
Abstract: Arginine–serine (RS) domain(s) in splicing factors are critical for protein–protein interaction in pre‐mRNA splicing. Phosphorylation of RS domain is important for splicing control and nucleocytoplasmic transport in the cell. RNA‐binding motif 20 (RBM20) is a splicing factor primarily expressed in the heart. A previous study using phospho‐antibody against RS domain showed that RS domain can be phosphorylated. However, its actual phosphorylation sites and function have not been characterized. Using middle‐down mass spectrometry, we identified 16 phosphorylation sites, two of which (S638 and S640 in rats, or S637 and S639 in mice) were located in the RSRSP stretch in the RS domain. Mutations on S638 and S640 regulated splicing, promoted nucleocytoplasmic transport and protein‐RNA condensates. Phosphomimetic mutations on S638 and S640 indicated that phosphorylation was not the major cause for RBM20 nucleocytoplasmic transport and condensation in vitro. We generated a S637A knock‐in (KI) mouse model (Rbm20 S637A ) and observed the reduced RBM20 phosphorylation. The KI mice exhibited aberrant gene splicing, protein condensates, and a dilated cardiomyopathy (DCM)‐like phenotype. Transcriptomic profiling demonstrated that KI mice had altered expression and splicing of genes involving cardiac dysfunction, protein localization, and condensation. Our in vitro data showed that phosphorylation was not a direct cause for nucleocytoplasmic transport and protein condensation. Subsequently, the in vivo results reveal that RBM20 mutations led to cardiac pathogenesis. However, the role of phosphorylation in vivo needs further investigation.